2018
DOI: 10.1093/nop/npy001
|View full text |Cite
|
Sign up to set email alerts
|

Survival in elderly glioblastoma patients treated with bevacizumab-based regimens in the United States

Abstract: Background The efficacy of bevacizumab (BEV) in elderly patients with glioblastoma remains unclear. We evaluated the effect of BEV on survival in this patient population using the Survival, Epidemiology, and End Results (SEER)-Medicare database. Methods This retrospective, cohort study analyzed SEER-Medicare data for patients (aged ≥66 years) diagnosed with glioblastoma from 2006 to 2011. Two cohorts were constructed: one com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Bevacizumab (BEV), another U.S. Food and Drug Administration (FDA) approved drug, is widely used for treatment in recurrent GBM. The survival benefits of TMZ and BEV have been widely explored in the clinical trials [8][9][10][11][12] and retrospective studies [13][14][15][16][17][18][19]. And, second-line chemotherapy options include nitrosoureas, lomustine, cyclophosphamide, irinotecan, and platinumbased regimens, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab (BEV), another U.S. Food and Drug Administration (FDA) approved drug, is widely used for treatment in recurrent GBM. The survival benefits of TMZ and BEV have been widely explored in the clinical trials [8][9][10][11][12] and retrospective studies [13][14][15][16][17][18][19]. And, second-line chemotherapy options include nitrosoureas, lomustine, cyclophosphamide, irinotecan, and platinumbased regimens, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors affecting the clinical prognosis, advanced age and poor general condition have always been associated with shorter global survival. 59…”
Section: Discussionmentioning
confidence: 99%
“…The poor prognosis and relative lack of clinical trials in elderly patients have led to uncertainty as to the optimal management of this group of patients. 9–13 The treatment decision in elderly patients can be difficult given other factors such as co-morbidities, co-medications and an increased susceptibility to side effects. In addition, the social and economic vulnerability typical of this type of population adds to said difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study showed older adults receive bevacizumab, a common treatment at recurrence, at much lower rates relative to the broader GBM population, although the patients who received bevacizumab experienced significantly improved survival. 15 …”
mentioning
confidence: 99%